Financial Skills and Women Entrepreneurial Motivation: A Mediating Role of Social Image - Pandey, Garima; Pandey, Gopal Prasad (The Lumbini Journal of Business and Economics, 2025)
Purpose: This study examines the impact of financial skills on women’s entrepreneurial motivation, focusing on mediating role of social image. Additionally, it analyzes the effect of financial literacy, self-efficacy, and risk-tolerance influence entrepreneurial motivations of women in Nepal. Methods: The study used descriptive and causal research design. The purposive sampling technique was done to survey 204 women entrepreneurs for this study. Data were collected through structured questionnaire distributed digitally. Statistical analysis was conducted using SPSS, and Excel. Descriptive statistics where data were gathered using six-point Likert scale, correlation, regression analysis to determine the relationships between variables. Results: The research found that book-keeping literacy and risk-tolerance positively affects women’s entrepreneurial motivation. However, the study revealed that Social image plays a mediating role, enhancing the influence of financial skills on motivation, particularly in context of financial literacy and risk-tolerance. Conclusion: Risk-taking and financial literacy are important factors that drive female entrepreneurs, and their influence is made even stronger by their social status. Enhancing financial literacy and addressing social norms can create supportive environment to female entrepreneurs in Nepal.